Transinterpret II: Transnational Quality Management in Heritage Interpretation Within the Framework of C. I. Leader+. The Case of Greece - Dorothea Papathanassiou-Zuhrt; Odysseas Sakellarides (European Regional Science Association (ERSA), 2006)
Natural und cultural heritage is commonly recognized as the major capital for sustainable tourism development. Many rural regions throughout Europe (UK, Germany, Switzerland, Italy), recognised the necessity to investigate widespread shortcomings and factors of success for the valorisation of local and regional heritage. Transinterpret I has been a successfully implemented transnational cooperation within the framework of C.I. Leader II that has established standards and recommendations concerning the quality of heritage presentation in a recreational learning environment. Transinterpret managed to improve practical applications in the field of heritage interpretation, especially in a visitor-friendly heritage presentation field with cognitive tools, validated by praxis and data. Projects and applications within Transinterpret are planned according to the standards and recommendations of a dynamically evolving database and are subjected to professional evaluation offered by checklists of the partner database and highly specialized human resources. The development of an international quality label for a visitor-centric Heritage Interpretation and further development of topics and planning issues related with interpretation as a sub-discipline of heritage management has been also a significant aim of the Transinterpret. In 2006 Greece has entered the second phase of Transinterpret - Transinterpret II. Priorities regarding tourism planning at local and regional level were -a novel form of managing heritage resources in order to create high added value tourism products, a wiser distribution of tourism expenditure, the creation of a distinct heritage tourism identity, which would not be conceived as an exchangeable commodity at global level. Creating and "exporting" place identity and place attachment was also a significant motive for Greek partners (Ipiros, Aitoloakarnania, Olympia, Drama, Xanthi, Rodopi, Kozani and Kastoria) to enter the cooperation. Being sustained by a Competence Centre operating nationwide, Greek partners will dynamically contribute to an innovative heritage management in their areas as well as in the partner areas. Through cognitive processing of information with tourism value and leisure time management in recreational learning environments for non captive audiences the partners aim to create attractive interpretive products and services, which would guarantee them visitor satisfaction, multipliers at local and regional level and a distinctive image confirmed by the Transinterpret II logo.
Keywords: 330